Efficacy of ultrasound-guided erector spinae plane block for analgesia after laparoscopic cholecystectomy: a randomized controlled trial - Altiparmak,Basak (2019)
Abstract Background and objectives: The primary aim of this study is to assess the effect of ultrasoung-guided erector spinae block on postoperative opioid consumption after laparoscopic cholecystectomy. The secondary aims are to assess the effects of erector spinae plane block on intraoperative fentanyl need and postoperative pain scores. Methods: Patients between 18-70 years old, ASA I-II were included in the study and randomly allocated into two groups. In Group ESP, patients received bilateral US-ESP with 40 ml of 0.25% bupivacaine at the level of T7, while in Group Control, they received bilateral US-ESP with 40 ml of saline before the induction of anesthesia. Then a standard general anesthesia procedure was conducted in both groups. NRS scores at the postoperative 15th, 30th, 60th minutes, 12th and 24th hours, intraoperative fentanyl need and total postoperative tramadol consumption were recorded. Results: There were 21 patients in Group ESP and 20 patients in Group Control. Mean postoperative tramadol consumption was 100 ± 19.2 mg in Group ESP, while it was 143 ± 18.6 mg in Group Control (p < 0.001). The mean intraoperative fentanyl need was significantly lower in Group ESP (p = 0.022). NRS scores at the postoperative 15th, 30th min, 12th hour and 24th hour were significantly lower in ESP group (p < 0.05). According to repeated measures analysis, NRS score variation over time was significantly varied between two groups (F[1, 39] = 24.061, p < 0.0005). Conclusions: Bilateral US-ESP block provided significant reduction in postoperative opioid consumption, intraoperative fentanyl need and postoperative pain scores of patients undergoing laparoscopic cholecystectomy.